Message of Social Criticism on Deforestation in the Lyrics of the Song 'Rat Tua' by FSTVLST - Pendana, Rabil Alberto; Urfan, Noveri Faikar (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The aim of this research is to understand the social criticism message about deforestation in Indonesia through the song "Rat Tua" by FSTVLST. The current climate crisis can already be felt, for example, through temperature changes and high rainfall. Raising awareness about the importance of this climate crisis issue requires various efforts, one of which can be through music. Fans of the band will surely understand and become aware of the issues brought by their favorite band. This research aims to dissect the critical message in the song "Rat Tua" with various metaphors and archaic or rarely used language. It employs Ferdinand De Saussure's semiotic analysis method with data collection techniques in the form of document studies. FSTVLST creates a song about trees but does not use the word "tree". It can be concluded that human actions are the main factor in the climate crisis. Human awareness of trees and forests is still lacking, and deforestation is evidence that humans are not improving the earth but worsening the impact of the climate crisis.